Lukšių šnektos žemutinių netrumpųjų balsių ypatumai - Bacevičiūtė, Rima (Kalbotyra, 1998)
The article examines some of the vocalism features of the Lukšiai subdialect. Lukšiai subdialect is attributed to the southern West-Aukštaitian dialect. The quantity, quality, pitch and intensity of the lower non-short vowels were subjected to experimental analysis.The vowels of different origin were found to have quantitative and qualitative differences. Positional and historical vowel continuance relation is 1 : 1.3 respectively. Qualitative vowels of the [a] type have lower F1 and F2, which may be a survival of their nasalization. The historical and positional vowel quality of [e] type differs, too.The curves of pitch and intensity confirm the differences: the curves of historical long vowels slightly rise, while the curves of positional vowels are falling.